ISOTHERM, KINETICS, AND THERMODYNAMIC STUDIES FOR ADSORPTION METHYLENE BLUE SOLUTION USING SHRIMP SHELL - Suci Wulandari; Hamdhan Fathony; Putri Ramadhani; Deswati; Rahmiana Zein (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
This research was carried out adsorption of methylene blue dye using shrimp shell (SS) biosorbent. Methylene blue dye is commonly used in the textile and paper industries. Previously, research had been carried out on the adsorption of anionic dyes by shrimp shells, then in this study a batch adsorption was carried out to absorb methylene blue cationic dyes.It is carried out in batches with several parameters to obtain the optimum conditions. Several studies were carried out such as isotherm studies, kinetics and thermodynamics to analyze how the adsorption process occurs. The adsorption process followed the Langmuir isotherm model for the two biosorbents which showed the formation of monolayers, the kinetic model followed the second-order pseudo. The thermodynamic study of shrimp shells showed that the adsorption process was non-spontaneous, endothermic, and increased randomness. FTIR analysis shows that there are electrostatic interactions, cation exchange, and hydrogen bonding. SEM-EDX analysis shows that the pore filling of the biosorbent surface by methylene blue molecules occurs.